Zebrafish: a novel model in neuropsychopharmacological research - Bhandari, Prasan Ramchandra (International Journal of Basic & Clinical Pharmacology, 2016)
The zebrafish (danio rerio) has recently become a powerful animal model for research purposes and drug discovery due to its ease of maintenance, genetic manipulability and ability for high-throughput screening. It has emerged as a model species for translational research in various neuroscience areas, including pharmacogenetics and neuropharmacology. Due to their physiological (neuroanatomical, neuroendocrine, neurochemical) and genetic homology to mammals, robust phenotypes, and value in high-throughput genetic and chemical genetic screens, zebrafish are ideal for developing valid experimental models of major neuropsychiatric disorders and discovering novel therapeutics. Both larval and adult zebrafish are presently used to enhance our understanding of brain function, dysfunction, and their genetic and pharmacological modulation. This article provides a review of the developing utility of zebrafish in the analysis of complex brain disorders (including, e.g., depression, autism, psychoses, drug abuse, and cognitive deficits), also covering zebrafish applications towards the goal of modelling major human neuropsychiatric and drug-induced syndromes.